Chlorination of bromide-containing waters: Enhanced bromate formation in the presence ofsynthetic metal oxides and deposits formed indrinking water distribution systems - Liu, C.; von Gunten, U.; Croué, Jean-Philippe (IWA Publishing, 2013)
Bromate formation from the reaction between chlorine and bromide in homogeneous solution is a slow process. The present study investigated metal oxides enhanced bromate formation during chlorination of bromide-containing waters. Selected metal oxides enhanced the decay of hypobromous acid (HOBr), a requisite intermediate during the oxidation of bromide to bromate, via (i) disproportionation to bromate in the presence of nickel oxide (NiO) and cupric oxide (CuO), (ii) oxidation of a metal to a higher valence state in the presence of cuprous oxide (Cu2O) and (iii) oxygen formation by NiO and CuO. Goethite (a-FeOOH) did not enhance either of these pathways. Non-charged species of metal oxides seem to be responsible for the catalytic disproportionation which shows its highest rate in the pH range near the pKa of HOBr. Due to the ability to catalyze HOBr disproportionation, bromate was formed during chlorination of bromide-containing waters in the presence of CuO and NiO, whereas no bromate was detected in the presence of Cu2O and a-FeOOH for analogous conditions. The inhibition ability of coexisting anions on bromate formation at pH 8.6 follows the sequence of phosphate>>sulfate>bicarbonate/carbonate. A black deposit in a water pipe harvested from a drinking water distribution system exerted significant residual oxidant decay and bromate formation during chlorination of bromide-containing waters. Energy dispersive spectroscopy (EDS) analyses showed that the black deposit contained copper (14%, atomic percentage) and nickel (1.8%, atomic percentage). Cupric oxide was further confirmed by X-ray diffraction (XRD). These results indicate that bromate formation may be of concern during chlorination of bromide-containing waters in distribution systems containing CuO and/or NiO.